Manajemen Strategik Dinas Perhubungan Kota Bukittinggi Dalam Meningkatkan Pendapatan Retribusi Parkir - Rahmad, Rahmad; Nasfi, Nasfi (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the factors that influence the increase in local revenue (PAD) of the City of Bukittinggi from parking fees, how to manage strategies in increasing parking fees. The study consisted of 2 stages, the Delphi method with 2 stages of interviews and SWOT analysis, to obtain information on the factors that influence the increase in parking fees and see the level of importance and effectiveness of the government's response. Informants are experts (experts) as many as 6 people and conduct a SWOT analysis to determine the right strategy. The research findings, the factors that influence the increase in parking fees, are seen from Strengths with an average score of 4.83 or 96.67 and the commitment of regional heads and ranks with an average score of 4.83 or 96.67. The level of effectiveness of the government's response is cooperation with other agencies with an average score of 3.83 or 76.67. Weaknesses factor average score of 5.00 or 100 The level of effectiveness of the government's response to parking attendants and supervisors who violate the rules with an average score of 4.17 is less effective. Opportunity factor with an average score of 5.00 or 100. The level of effectiveness of the government's response is the advancement of information technology with an average score of 4.17. Threaths with the highest level of importance were thuggery and unscrupulous officers with an average score of 4.83. Based on the level of effectiveness of the government's response is natural conditions (pandemic) with an average score of 4.17 or 83.33 with Effective criteria.